Synthesis of Nickel(II) Complexes Using α,β-Conjugated Schiff Base Compounds - Nadarajan, Priya (Universiti Malaysia Sarawak (UNIMAS), 2015)
Two types of α,β-conjugated Schiff base compounds with different R substituents were synthesized by the condensation reaction of cinnamaldehyde with aniline (1) and 4methoxycinnamaldehyde with 4-methoxyaniline (2) in the presence of ethanol. Then, the α,βconjugated Schiff bases (1-2) were allowed to react with NiCl2·6H2O to produce nickel(II) complexes (3-4). The α,β-conjugated Schiff bases (1-2) and their complexes (3-4) obtained were characterized using Fourier Transform Infrared (FTIR), UV-Vis spectroscopy, CHN analyser and 1H Nuclear Magnetic Resonance (1H NMR). Both the α,β-conjugated Schiff bases (1-2) and complexes (3-4) are polar in nature. Spectral studies suggested that α,βconjugated Schiff base compounds (1-2) acted as a bidentate ligand towards nickel(II) ion and metal complex 4 was suggested to demonstrate a square planar geometry.